2020
DOI: 10.1186/s40729-020-00231-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of antihypertensive medications on the clinical parameters of anodized dental implants: a retrospective cohort study

Abstract: Background: Hypertension is a chronic medical condition in which blood pressure in the arteries is elevated. Given the large proportion of dental implant patients using antihypertensive medications, it is crucial to evaluate the effects of these drugs on the clinical parameters of osseointegrated implants. The aim of the present retrospective cohort study was to evaluate the influence of antihypertensive medications on clinical peri-implant tissue parameters. Methods: Thirty-five patients received a total of 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 23 publications
0
20
0
1
Order By: Relevance
“…However, no subgroup analysis was performed, limiting definitive conclusions on this topic. Another recent retrospective cohort study found higher peri-implantitis rates and higher deep-pocket rates in patients prescribed with antihypertensive drugs [49]. Also here, the authors did not discriminate between the different antihypertensive drug classes, and the study further focused on other outcome measures, thus, limiting the comparability with the present study.…”
Section: Discussionmentioning
confidence: 70%
“…However, no subgroup analysis was performed, limiting definitive conclusions on this topic. Another recent retrospective cohort study found higher peri-implantitis rates and higher deep-pocket rates in patients prescribed with antihypertensive drugs [49]. Also here, the authors did not discriminate between the different antihypertensive drug classes, and the study further focused on other outcome measures, thus, limiting the comparability with the present study.…”
Section: Discussionmentioning
confidence: 70%
“…That can be answered by Seki et al who found a negative effect of anti-hypertensive drugs on dental implants and hypothesized that bone metabolism is affected and thus deeper pockets were observed and more bone resorption. 40 That contradicted other authors who believed that drugs used for systemic diseases namely the anti-coagulants (that could be taken by some hypertensive patients) might have some protective role against peri-implant diseases, due to their secondary anti-inflammatory effects, this is what Romandini et al believed, 41 Nemati et al found out an anti-inflammatory effect for the anti-hypertensive drugs could also enhance the function of PMN’s immune cells, 42 this could contribute to a better understanding of the better scores of the patients with systemic diseases when compared to systemically healthy patients in this article.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the success rate in the hypertensive group for medicated users was lower (92.5%) than that for nonmedicated users (94.1%), without a significant difference ( p = 0.939) 355 . A retrospective study reported higher bone loss, greater pocket depth, and higher prevalence of peri‐implantitis in patients under antihypertensive treatment (0.66 mm of bone loss and 30.8% of patients with peri‐implantitis) than in healthy patients (0.34 mm of bone loss and 9.1% of patients with peri‐implantitis) 356 . Calcium channel‐blocking agents may induce gingival hyperplasia with alterations in MMP metabolism and failure of collagenases activation 356 .…”
Section: Drug‐related Factors Affecting Bone Metabolismmentioning
confidence: 96%
“…355 A retrospective study reported higher bone loss, greater pocket depth, and higher prevalence of peri-implantitis in patients under antihypertensive treatment (0.66 mm of bone loss and 30.8% of patients with peri-implantitis) than in healthy patients (0.34 mm of bone loss and 9.1% of patients with peri-implantitis). 356 Calcium channelblocking agents may induce gingival hyperplasia with alterations in MMP metabolism and failure of collagenases activation. 356 Finally, a recent systematic review about the topic, included only 3 studies and 959 patients.…”
Section: Antihypertensivesmentioning
confidence: 99%
See 1 more Smart Citation